Postharvest quality of papaya fruit (carica papaya)associated with applications of calcium and chitosan - Ali Ahmed Al Eryani, Abdul Raqeeb (2008)
A study was conducted to evaluate calcium and chitosan effects on storage life, anthracnose disease incidence, quality, physiological changes and enzymes activities of papaya. Mature green papaya fruits of colour index 2 were used for conducting the experiments. In the first experiment, papaya fruits were treated with different concentrations of chitosan, 0, 0.5, 0.75 and 1%, and stored at 13±1°C for 28 days. Chitosan concentrations 0.75 and 1% showed the best effect on extending storage life by 26 and 28 days, respectively while maintaining the quality compared with 0.5% and control. However, there was no significant difference between 0.75 and 1% treatments. In the second experiment, calcium at different concentrations 1.5, 2.5 or 3.5% were applied as a postharvest treatment for papaya fruits using vacuum infiltration and dip application techniques. Calcium infiltration at 2.5% significantly extended the storage life up to 26 days and retained the quality better than other treatments. Since, chitosan with its coating ability to retard weight loss of fruits and antifungal property while alcium provides better fruit firmness, a study was conducted using calcium at different concentrations 1.5, 2.5 or 3.5% and chitosan at 0.75% or their combination. From the in vitro experiment, calcium at different concentrations had slight inhibition effects on C. gloeosporioides spore germination but did not show any significant effects on mycelial growth. Chitosan treatment significantly inhibited spore germination and mycelia growth compared to calcium treatments and their control. Calcium at 2.5 in combination with chitosan (0.75%) had significantly better effects on inhibition of spore germination and mycelial growth of C. gloeosporioides compared to calcium individual treatments. Anthracnose disease incidence (%) on papaya fruits was significantly controlled (5.6%) using calcium at 2.5% and chitosan compared with the other treatments. This combined treatment of 2.5% calcium with chitosan 0.75% extended the storage life up to 33 days while retaining the quality of fruits compared with the other treatments. To look at the effect of this combined treatment over different storage intervals, experiment has been conducted. The effectiveness of the treatments was assessed by evaluating their impacts on the quality characteristics during 35 days of storage period. Calcium 2.5% in combination with chitosan 0.75% treatment had better retention of fruits firmness, weight loss, retarding changes in color and preserving chemical characteristics during storage compared to the other treatments. Furthermore, experiment on the physiological and ultrastructures changes and enzyme activities during storage was conducted. The combined treatment of calcium 2.5% and chitosan 0.75% markedly reduced the respiration rate, ethylene production and maintaining the integrity of the waxy cuticle and epidermal cells. Polygalacutronase (PG) degrading enzyme activity was retarded and the induction of defense response of fruits against anthracnose disease was enhanced by eliciting peroxidase enzyme activities (POD).